The Identification of the Causes of Business Cycles Across Countries - Schlagenhauf, Don (IMF Working Papers; Working Paper ;, 1990)
Empirical research has been conducted on the various theories of the business cycle over many countries. However, very little research has attempted to undertake a multi-country disaggregate investigation into the sources of output change. This paper decomposes fluctuations in industry output in a particular country into: (1) a nation specific shock; (2) an industry specific shock; (3) a world shock; and (4) an idiosyncratic factor. Using a dynamic factor analysis-state-space approach, the paper finds that the nation-specific shock is the most important impulse.